Surface-induced demixing of self-assembled isomeric mixtures of citral - Saraf, Deepashri; Prakash, Shikha; Pinjari, Aadil; Pujari, Bhalchandra; Sengupta, Durba (Journal of Molecular Liquids, 2023)
The self-assembly of organic molecules and their interactions with metal surfaces have been of considerable interest, both for developing novel functional materials and for understanding fundamental design principles of nanostructures. In this study, we investigate the solution and surface-induced self-assembly of two stereoisomers of citral molecules (geranial and neral) using atomistic molecular dynamics simulations. We demonstrate that the morphology of the aggregates in water is concentration dependent (ranging from distorted spherical to slab-like aggregates) but independent of isomer effects. The isomeric mixtures of citral indicate homogeneous mixing based on differential density maps and high values of Shannon entropy. Interestingly, surface-confinement of citral aggregates on a Cu(111) surface leads to phase segregation and demixing of the two isomers that is more apparent in the surface-bound monolayer in comparison to the adjacent layers. Positional ordering and formation of domains are observed over a series of isomeric citral mixtures with varying compositions, as indicated by high differential density and low values of Shannon entropy. Our work provides new insights into molecular self-assembly of organic molecules in nanostructures and metal-organic overlayers.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Citral; Isomers; Metal-organic interactions; molecular dynamics; Self-assembly; Shannon entropy